2016
DOI: 10.1016/j.jare.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of calcium phosphate composite nanoparticles in targeting Ehrlich carcinoma cells transplanted in mice

Abstract: The present study aimed to investigate the mode of action of nano-CaPs in vivo as a therapy for solid tumor in mice. To achieve this goal, Ehrlich Ascites Carcinoma (EAC) was transplanted into 85 Swiss male albino mice. After nine days, the mice were divided into 9 groups. Groups 1 and 2 were allocated as the EAC control. Groups 3 and 4 were injected once intratumorally (IT) by nano-calcium phosphate (nano-CaP). Groups 5 and 6 received once intraperitoneal injection (IP) of nano-CaP. Groups 7, 8, and 9 receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
(33 reference statements)
0
5
0
1
Order By: Relevance
“…The calcium phosphate adjuvanted Omps nanoparticles formulated in this study had a size of 20–50 nm and were spherical in morphology. Similar nanoparticles were used earlier for drugs and antigen delivery [25, 38, 39]. Though in few reports, variation in size of nanoparticles was reported due to differences in frequency of stirring and pH of the suspension [24].…”
Section: Discussionmentioning
confidence: 94%
“…The calcium phosphate adjuvanted Omps nanoparticles formulated in this study had a size of 20–50 nm and were spherical in morphology. Similar nanoparticles were used earlier for drugs and antigen delivery [25, 38, 39]. Though in few reports, variation in size of nanoparticles was reported due to differences in frequency of stirring and pH of the suspension [24].…”
Section: Discussionmentioning
confidence: 94%
“…Oxidative stress markers (GSH; (OD 412 ), GPx (OD 340 ); CAT (OD 520 )) and a lipid peroxidation marker (MDA; OD 532 ) were analyzed in vehicle control and N-SNPs-treated group tissues as previously mentioned [6,33,40,41]. In brief, the extracted EAC tumors were washed several times with ice-cold phosphate buffer saline and tissue lysates were prepared by homogenizing in lysis buffer (50 mM Tris, pH 7.5, 150 mM NaCl, 1% Triton X-100, 0.1% sodium dodecyl sulfate (SDS)).…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…Keskin et al demonstrated that cell-free culture media of Synechococcus sp. had a reducible activity that resulted, under light conditions, in the formation of Ag-NPs with an average nanosize of 140 nm [ 64 ]. However, this process is sometimes unsuitable for NP synthesis because many types of media used for the culture of microorganisms contain components that act as reductants and stabilizing agents.…”
Section: Synthesis Routes Of Nanoparticlesmentioning
confidence: 99%